GAMBARAN RESILIENSI PADA REMAJA KORBAN CYBERBULLYING - Mubaroq, Fariz; Huda, Nurul; Weliangan, Hally (Arjwa: Jurnal Psikologi, 2024)
This research aims to explain the level of resilience in adolescents who have been victims of cyberbullying. The method used is descriptive quantitative by sending surveys trough Google Forms. The research respondents consists of 73 adolescents aged between 13 to 18 years who have experienced cyberbullying. The measurement instrument tool used in this study refers to the aspects of resilience according to Connor and Davidson (2003), which include of personal competence, trust in instinct, positive acceptance of change and secure relationship, self-control and factors, and spiritual influences. The analysis results show that the empirical average resilience score is 101.45, classified as high with a standard deviation of 19.16. High resilience levels indicate that adolescents who are victims of cyberbullying have the ability to cope and recover from negative impacts such as stress and depression. This is reflected in the high personal competence of cyberbullying victims, including the ability to manage emotions, make appropriate decisions, and build healthy interpersonal relationships. They also have strong trust in their instincts, which includes belief in their own ability to overcome problems and face challenges. Good self-control also supports resilience because adolescents who are victims of cyberbullying can control their emotions and behaviors, making it easier for them to recover from traumatic experiences. Addiotionally, high social support plays a crucial role as it provides support and attention, helping these adolescents feel supported and not alone in facing their problems. Furthermore, spiritual influence with belief in assistance from the divine being indicates that these adolescents have spiritual beliefs and trust in higher power to be a source of strength and calmnessin facing difficulties.